A Self‐Adjuvanting Supramolecular Vaccine Carrying a Folded Protein Antigen. Issue 8 (August 2013) - Hudalla, Gregory A.; Modica, Justin A.; Tian, Ye F.; Rudra, Jai S.; Chong, Anita S.; Sun, Tao; Mrksich, Milan; Collier, Joel H.
<x xml:space="preserve">Abstract</x> This work illustrates a strategy for the design of molecularly defined immunotherapies, using a blend of supramolecular peptide self‐assembly and active site‐directed protein capture. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>